The Effectiveness of Pregnant Women Class to Increase Knowledge and Hemoglobin Level - Husna, Putri Halimu; Purwandari, Kristiana Puji; Mawarni, Siti; Sundari, Sri; Wardani, Indah Kusuma; Maryati, Maryati (Journal of Maternal and Child Health, 2020)
Background: Intrauterine Fetal Death (IUFD) is a birth process of a conception result in a state of death. It is also a contributor to death for Infant Mortality Rate (IMR). Pregnant Woman Class is a government effort to reduce IMR. However, the implementation has not been maximized. This stu